Financing municipal tasks in Slovenia - Brezovnik, Boštjan (Array, 2019)
The paper examines whether the system implemented for financing local communities (municipalities) in Slovenia in the period 2010-2016 is compliant with the European Charter of Local Self-Government. We examined the cost coverage for performing the tasks of municipalities, the cost structure and the rate of interconnections between the budgeted funds under the eligible expenditure mechanism and the data collected on costs by municipality. Our hypothesis states that theprinciples whereby funding would be commensurate with tasks were not fulfilled in the period between 2010 and 2016 in the Republic of Slovenia given that the average per capita costs exceeded the funding under eligible expenditure. The discrepancy had increased from the previously examined period of 2007-2009. The findings show that although the principles of the European Charter of Local Self-Government have been satisfactorily included in the country’s laws, certain discrepancies have been found with regard to funding where the principle of municipal funding had not adequately been taken into account to ensure that funding is commensurate with the tasks. Between 2010 and 2016, municipalities received less funding than the scope of their tasks would require. The situation deteriorated in 2010–2016with respect to the 2007–2009 period when the existing funding model was introduced. The municipal funding model should be improved so that the eligible expenditure calculation takes into account inreal time the real costs needed to perform the tasks of local communities; and the cost structure should be made more homogeneous. The model should be changed to consider and enable the performance of development tasks of municipalities through investments.